2017
DOI: 10.3906/biy-1706-45
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin positively regulates the immunosuppressive capabilitiesof adipose-derived mesenchymal stem cells

Abstract: IntroductionAdipose-derived mesenchymal stem cells (Ad-MSCs) are highly multipotent cells with a high potential for differentiation into multiple cell types (Vieira et al., 2010;Park et al., 2012;Mellor et al., 2015). Ad-MSCs produce various growth factors that contribute to injury healing and tissue regeneration (Salgado et al., 2010). The antiinflammatory, immunomodulatory, and antioxidant properties of mesenchymal stem cells (MSCs) make them desirable candidates for cell-based therapies (Soleymaninejadian e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[ 40 ] Current and nascent separation techniques include tangential flow filtrations (TFF), counterflow centrifugation elutriations (CCE), and dead‐end sieving; these require sophisticated equipment for such separation process. [ 42 ] Simpler membrane‐based filtration faces the disadvantage of clogging (cake formation) during the cell–particle separation step. [ 25 ] Membrane‐less separation approaches such as microfluidic‐based sorting have also been explored to separate cells from particles; [ 40 ] nevertheless, this additional cell–particle separation step is time‐consuming and can present contamination or dead volume (cell loss) risks with the incorporation of another microfluidic module into the cell manufacturing workflow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 40 ] Current and nascent separation techniques include tangential flow filtrations (TFF), counterflow centrifugation elutriations (CCE), and dead‐end sieving; these require sophisticated equipment for such separation process. [ 42 ] Simpler membrane‐based filtration faces the disadvantage of clogging (cake formation) during the cell–particle separation step. [ 25 ] Membrane‐less separation approaches such as microfluidic‐based sorting have also been explored to separate cells from particles; [ 40 ] nevertheless, this additional cell–particle separation step is time‐consuming and can present contamination or dead volume (cell loss) risks with the incorporation of another microfluidic module into the cell manufacturing workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Gelatin has also been demonstrated as a substrate for 2D monolayer culture, for which others have found that adipogenesis and osteogenesis differentiation were enhanced. [ 41,42 ] This suggested that gelatin is a suitable substrate for the growth of MSC while maintaining cell differentiation capacity and multipotency. Also, as gelatin has been demonstrated as a safe material for human exposure and consumption (at least as an edible), there is relatively low but to no risk in the delivery of any highly degraded gelatin with the therapeutics of cell suspension.…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, the third passage of cells was used as an allograft. These cells had previously been identified as having multilineage differentiation capabilities [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The third passage (P3) of Ad-MSCs was used in subsequent experiments [21]. These cells have been previously confirmed for their multiline differentiation capability [16, 22].…”
Section: Methodsmentioning
confidence: 99%